Identifying the Interaction between Foreign Investor Flows and Emerging Stock Market Returns - Ülkü, Numan; Weber, Enzo (Review of Finance, 2014)
Abstract We introduce the structural conditional correlation (SCC) methodology to the foreign flows literature to identify the contemporaneous return–flow interaction and provide new evidence using the first daily data from a sizeable European emerging market and comparing to Asian markets. SCC results indicate significant bilateral intraday interaction between net foreign flows and market returns, and the presence of their latent common drivers. Allowing for these effects alters previously uniform results of positive feedback trading for some Asian markets, as well as the price impact estimates. Foreigners display a sluggish response to global information, which cannot be attributed to their information disadvantage.